2020
DOI: 10.1136/gutjnl-2019-319866
|View full text |Cite
|
Sign up to set email alerts
|

Image-based consensus molecular subtype (imCMS) classification of colorectal cancer using deep learning

Abstract: ObjectiveComplex phenotypes captured on histological slides represent the biological processes at play in individual cancers, but the link to underlying molecular classification has not been clarified or systematised. In colorectal cancer (CRC), histological grading is a poor predictor of disease progression, and consensus molecular subtypes (CMSs) cannot be distinguished without gene expression profiling. We hypothesise that image analysis is a cost-effective tool to associate complex features of tissue organ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
155
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(159 citation statements)
references
References 26 publications
4
155
0
Order By: Relevance
“…The consensus molecular subtypes (CMS) transcriptionally distinguish four groups of colorectal cancer with different clinical behaviors and biology, so Sirinukunwattana et al [ 76 ] trained a model to designate image-based CMS (imCMS) classes to HE-stained slides. The authors used two resection cohorts (TCGA, FOCUS) and one biopsy cohort (GRAMPIAN), and patches were extracted from WSI regions annotated by pathologists to be tumor.…”
Section: Beyond the Pathologist—features Invisible To The Human Eye ?mentioning
confidence: 99%
See 1 more Smart Citation
“…The consensus molecular subtypes (CMS) transcriptionally distinguish four groups of colorectal cancer with different clinical behaviors and biology, so Sirinukunwattana et al [ 76 ] trained a model to designate image-based CMS (imCMS) classes to HE-stained slides. The authors used two resection cohorts (TCGA, FOCUS) and one biopsy cohort (GRAMPIAN), and patches were extracted from WSI regions annotated by pathologists to be tumor.…”
Section: Beyond the Pathologist—features Invisible To The Human Eye ?mentioning
confidence: 99%
“…This study by Sirinukunwattana et al [ 76 ] offered two additional novelties in CMS classification. First, patches with high prediction confidence for imCMS subtypes could be extracted to examine histological patterns.…”
Section: Beyond the Pathologist—features Invisible To The Human Eye ?mentioning
confidence: 99%
“…CNN algorithms were used to predict RNA expression classifiers from H&E images. This work lays the foundation for a comprehensive integration of morphology and molecular features[ 32 ]. Immunohistochemical staining and fluorescence microscopy belong to members of pathological examinations, and ANNs distinctly improved their diagnostic performance in GI tumors[ 33 - 35 ].…”
Section: Achievements Of Ann Research In Gi Diseasesmentioning
confidence: 99%
“…Specimens of various GI cancers can be processed to identify molecular markers that may predict responses to targeted therapies. Research has shown that certain clinically relevant molecular alterations in GI cancers are associated with specific histopathological features detected on hematoxylin-eosin (HE) slides; there have been some successful attempts to adopt AI applications for HE sections as surrogate markers for these alterations[ 31 - 34 ].…”
Section: Ai-applications In Gi Pathologymentioning
confidence: 99%
“…The DL algorithm demonstrated an AUC of 0.96 in the multi-institutional validation cohort. Furthermore, the consensus molecular subtype of colorectal cancer could be predicted from the images of colorectal surgical specimens using a CNN-based model[ 31 ]. Although prediction of molecular alterations by AI application might seem attractive, as clinically relevant biomarkers cannot be identified using HE stained slides and conventional PCR assay are both expensive and time-consuming, AI can neither achieve complete concordance with the gold standard test nor replace it.…”
Section: Ai-applications In Gi Pathologymentioning
confidence: 99%